Usefulness of an Image Fusion Model Using Three-Dimensional CT and MRI with Indocyanine Green Fluorescence Endoscopy as a Multimodal Assistant System in Endoscopic Transsphenoidal Surgery - Akihiro Inoue; Takanori Ohnishi; Shohei Kohno; Naoya Nishida; Yawara Nakamura; Yoshihiro Ohtsuka; Shirabe Matsumoto; Shiro Ohue (International Journal of Endocrinology)
Purpose. We investigate the usefulness of multimodal assistant systems using a fusion model of preoperative three-dimensional (3D) computed tomography (CT) and magnetic resonance imaging (MRI) along with endoscopy with indocyanine green (ICG) fluorescence in establishing endoscopic endonasal transsphenoidal surgery (ETSS) as a more effective treatment procedure. Methods. Thirty-five consecutive patients undergoing ETSS in our hospital between April 2014 and March 2015 were enrolled in the study. In all patients, fusion models of 3D-CT and MRI were created by reconstructing preoperative images. In addition, in 10 patients, 12.5 mg of ICG was intravenously administered, allowing visualization of surrounding structures. We evaluated the accuracy and utility of these combined modalities in ETSS. Results. The fusion model of 3D-CT and MRI clearly demonstrated the complicated structures in the sphenoidal sinus and the position of the internal carotid arteries (ICAs), even with extensive tumor infiltration. ICG endoscopy enabled us to visualize the surrounding structures by the phasic appearance of fluorescent signals emitted at specific consecutive elapsed times. Conclusions. Preoperative 3D-CT and MRI fusion models with intraoperative ICG endoscopy allowed distinct visualization of vital structures in cases where tumors had extensively infiltrated the sphenoidal sinus. Additionally, the ICG endoscope was a useful real-time monitoring tool for ETSS.